The Roots of Single Parenting and Its Influence on the Socioeconomic Trajectories of Young Adults in Uyo, Akwa Ibom State, Nigeria - Ngozi U. Nwonye; Victoria V. Nkan; Ann E. Dijeh (International Journal of Home Economics, Hospitality and Allied Research)
This study investigates the causes and multifaceted impacts of single parenting on the socio-economic development of young adults in Uyo, Akwa Ibom State, Nigeria. This context, often overlooked in global family dynamics research, is increasingly relevant as urbanization accelerates. A quantitative research design was employed, and data were collected from 399 respondents, including both academic and non-academic staff, through structured questionnaires. The study found that the primary drivers of single-parent households in the region are divorce (49.6%) and widowhood (40.1%).Young adults from single-parent families face significant challenges, including heightened risks of social stigma, economic hardship, and educational disparities. These challenges were reflected in clustered mean scores of 2.715 for social impact and 2.729 for economic impact. The study also highlighted gendered perceptions, revealing that social adjustment and career outcomes are shaped by both gender and family structure. Female respondents, in particular, reported greater difficulties in social integration and career progression. A unique aspect of this study is its localized focus on the dynamics of single-parenting in a rapidly urbanizing Nigerian city. The findings underscore the critical need for targeted interventions at both policy and community levels to address the specific challenges faced by young adults in these households. Recommendations include enhancing support networks, improving access to mental health services, and offering financial aid for educational advancement. The study emphasizes the importance of developing tailored interventions that foster resilience among young adults from single-parent households. By addressing systemic challenges, these interventions could play a vital role in promoting socio-economic inclusion and informing more inclusive policies in Nigeria’s rapidly changing socio-economic landscape.